Heat transfer enhancement of laminar flow in a circular tube using Swirl/vortex generator - Sami D. Salman,; Abdul Amir H. Kadhum,; Mohd S. Takriff,; Abu Bakar Mohamad, (Fakulti Kejuruteraan ,UKM,Bangi., 2014)
Swirl/vortex fl ow generator is an important form of passive augmentation techniques consist of a variety of tube inserts, geometrically varied fl ow arrangements and duct geometry modifi cations that produce fl ows. Twisted-tape is one of the most important members of this form which used extensively in different type heat exchangers. This paper presents a research on heat transfer enhancement and friction factor characteristics in a circular tube using CFD simulation. Plain twisted tape inserts with twist ratios (y = 2.93, 3.91) and slant baffl ed twisted tape inserts with baffl e angle 30° and twist ratio (y = 2.93) have been used for the simulation. The results obtained by simulation matched with the literature correlations for plain tube with the discrepancy of less than ±8% for Nusselt number and ±6.25% for friction factor. The results have also revealed that the heat transfer in term of the Nusselt number enhanced with increases of Reynolds number, decreases of twist ratio. Among the various twist ratios, the slant baffl ed twisted tape with twist ratio of y = 2.93 has offered a maximum heat transfer enhancement with signifi cant friction factor.